The effects of social sustainable supply chain management practices on societal value and carbon footprint reduction: implications for fisherman ecosystems - Fernando, Yudi; Jabbour, Charbel Jose Chiappetta; Noor Asnida, Amri; Mohd Ridzuan, Darun (2019)
Malaysia has spent for environmental protection and manufacturing industry are the highest contributor for environmental protection expenditure. The environmental protection expenditure has covered activities such as pollution prevention, waste management and also environmental monitoring. This indicates that manufacturing industries are highly exposed to environmental damage activities in their daily business operation. Despite on guidance and incentives offered by government to promote sustainability development, Malaysian manufacturing firms still facing challenge to leverage environmental value. Consequently, this problem possibly leads to downgrade the manufacturing companies’ sustainability performance. As sustainability awareness and expectation keep on increasing especially in emerging countries, manufacturing firms are encouraged to be more responsible towards their footprint on environment and social aspects. Local government has encouraged the manufacturing firms to contribute to the development of the society. Yet, the effectiveness of the social sustainable supply chain management practices gained less attention. The objective of paper is to investigate the research question on how social sustainable supply chain management has been practices by manufacturing firms able to improve societal value to fisherman ecosystems and reduce carbon footprint. The sample was the small medium size manufacturing industry which located in east coast region of Malaysia and participated actively for development of fisherman under programme of green corporate social responsibility. A web based survey was used to collect data from 105 manufacturing firms with ISO 14001 certification. The statistical analysis found that social monitoring, social management system and social new product and process development has a positive relationship on societal value and carbon footprint reduction. This study suggest that manufacturing firms need to contribute more to development of traditional fisherman ecosystems and improve their income with usage of modern technology.